Impact of daily octenidine skin washing versus nonwashing on antiseptic tolerance of coagulase-negative staphylococci in two neonatal intensive care units with different skin cleansing practices - Heather Felgate; Charlotte Quinn; Ben Richardson; Carol Hudson; Dheeraj Sethi; Sam Oddie; Paul Clarke; Mark A. Webber (Elsevier, 2024)
Summary: Background: There is wide variation in practices regarding routine bathing/washing of babies in neonatal intensive care units (NICUs). Evidence is lacking as to the benefit of routine antiseptic washes for reducing infection. We aimed to compare the antiseptic tolerance of Coagulase Negative Staphylococci (CoNS) within two UK NICUs with very different approaches to skin washing. Methods: We compared antiseptic susceptibility of CoNS isolated from skin swabs of neonates admitted to the Norfolk and Norwich University Hospital (NNUH) NICU in December 2017-March 2018 with those isolated in the Bradford Royal Infirmary (BRI) NICU in January-March 2020. The NNUH does not practise routine whole-body washing whereas BRI practises daily whole-body washing from post-menstrual age 27 weeks using Octenisan wash lotion (0.3% octenidine; 1 minute contact time before washing off with sterile water). A total of 78 CoNS isolates from BRI and 863 from the NNUH were tested for susceptibility against the antiseptics octenidine (OCT) and chlorhexidine (CHX). Results: Isolates from the BRI with practice of routine washing did not show increased antiseptic tolerance to OCT or CHX. Isolates from the NNUH which does not practise routine whole-body washing and rarely uses octenidine, were comparatively less susceptible to both CHX and OCT antiseptics. Conclusions: Daily whole-body skin washing with OCT does not appear to select for CoNS isolates that are antiseptic tolerant towards OCT and CHX. There remains considerable uncertainty about the impact of different antiseptic regimes on neonatal skin microbiota, the benefit of routine washing, and the development of antiseptic tolerance in the NICU.